An isobar-surfaces approach to multidimensional outlier-proneness - Marie-Francoise Barme-Delcroix; Ursula Gather (Universität Dortmund, Sonderforschungsbereich 475 - Komplexitätsreduktion in Multivariaten Datenstrukturen, 2000)
The aim of this paper is to define and investigate outlier-proneness for multivariate distributions. This is done by using a concept of ordering multivariate data based on isobar-surfaces, which yields an utmost analogy of the results to the univariate case.
Keywords: 519; isobars; order statistics; extreme values; weak stability; outliers; outlier-proneness